Analisis Dampak Hutan Rakyat Bersertifikat Legal di Desa Semoyo Kecamatan Patuk Kabupaten Gunungkidul Daerah Istimewa Yogyakarta - Rahmaningrum, Ririn Nadia, Dr. Kuswaji Dwi Priyono, M. Si, Agus Anggoro Sigit, S. Si, M. Sc (2016)
Forests are a natural asset that should be preserved because many benefits gained by their forests. Timber Legality Verification System (SVLK) promising legal forest products, abundant, and environmentally sustainable. This study aims to analyze Shareable private forests (TLVs), analyze the characteristics of community forests SVLK, and analyze the impact of the existence of community forests SVLK ioeconomic residents SVLK members. The method used to analyze Shareable community forests and community forests SVLK analyze the characteristics, namely with field surveys and interviews. The method used to analyze the impact of the existence of community forests SVLK socioeconomic using tabular analysis. SVLK people forest spread over 5 hamlets that Brambang, Salak, Pugeran, Semoyo and Wonosari this because members of SVLK have land spread throughout the region. In Wonosari village community forests SVLK patterned clustered, because the public forests belong to the same person. haracteristics Semoyo private forests consist of non-public forests, community forests and community forests subsidies Special Allocation Fund. Type the garden plants in the mix, this is because farmers want to get the lots on less land. Harvesting system used is a combination of selective logging and cutting need. SVLK social impact with the emergence of new groups that serve to cultivate and regulate forestry governance. SVLK economic impact could increase the selling price of wood SVLK range from Rp 100,000 - Rp 200,000 to Rp 400,000 - Rp 700,000 and making timber sales distribution becomes wider to overseas